THE IMPORTANCE OF A BUSINESS PLAN IN BUILDING A BUSINESS - Sherly Etika Sari; Zuhratul Aulia; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Business planning is a very important aspect for someone who is starting a business or entering the world of entrepreneurship. Entrepreneurship is not enough just to have confidence, it requires business planning. Running a business, especially a new business, is impossible without a prior plan. Business planning is an important step before executing any business strategy. Companies created it to help them consider all the elements they need to make their business successful. The research used in this research is library research which contains theories related to the problem being studied. In this section, an evaluation of the ideas and concepts used is carried out based on accessible literature. This research discusses the definition and importance of entrepreneurship in the economy, the meaning and objectives of a business plan, the main components in a business plan, and business plans influencing strategic and operational decisions in business.